Vision testing is additive to the sideline assessment of sports-related concussion. Issue 1 (February 2015) - Marinides, Zoe; Galetta, Kristin M.; Andrews, Connie N.; Wilson, James A.; Herman, Daniel C.; Robinson, Christopher D.; Smith, Michael S.; Bentley, Brett C.; Galetta, Steven L.; Balcer, Laura J.; Clugston, James R.
Abstract : Summary: We examined the King-Devick (K-D) test, a vision-based test of rapid number naming, as a complement to components of the Sport Concussion Assessment Tool, 3rd edition (SCAT3) for diagnosis of concussion. Baseline and postconcussion data for the University of Florida men's football, women's soccer, and women's lacrosse teams were collected, including the K-D test, Standardized Assessment of Concussion (SAC), and Balance Error Scoring System (BESS). Among 30 athletes with first concussion during their athletic season (n = 217 total), differences from baseline to postinjury showed worsening of K-D time scores in 79%, while SAC showed a ≥2-point worsening in 52%. Combining K-D and SAC captured abnormalities in 89%; adding the BESS identified 100% of concussions. Adding a vision-based test may enhance the detection of athletes with concussion.